Utilization of High kV Lumbar Examination Technique in Determination of Entrance Surface Dose (ESD) - Budiwati, Trisna; Andriani, Intan (Sean Institute, 2022)
Entrance Surface Dose (ESD) is one of the units of quantity used in diagnostics to express the radiation dose received by the object (phantom or patient) measured at the centre of the main beam on the surface of the phantom or patient (UNSCEAR, 2010). According to Bushong (2008), the high kV technique states that to get the same optical density, with an increase in tube voltage (kV) of 15%, a 50% decrease in the mAs value is required. This study aims to calculate the ESD value if applied in the use of the high kV technique in lumbar irradiation using the Cobia Smart R/F measuring instrument. In this study, the authors applied the high kV technique using 65 kV and 16 mAs, 75 kV and 8 mAs, and 85 kV and 4 mAs. The dose value measured in the Cobia Smart R/F tool is then entered into the formula to calculate the Entrance Surface Dose (ESD) value. The results showed that the Entrance Surface Dose (ESD) produced at 65 kV, 75 kV, and 85 kV, respectively, were: 1.3597 mGy, 0.9728 mGy, and 0.7055 mGy. From the Diagnostic Reference Level (DRL) data released by BAPETEN in 2020, it is known that the DRL value for the Lumbar AP examination is 1.8 mGy. In this case, the high kV technique can minimize the dose to the examined object.